2013
DOI: 10.1007/s00402-013-1694-9
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual cross-cultural adaptation of the patient-rated wrist evaluation (PRWE) into Czech, French, Hungarian, Italian, Portuguese (Brazil), Russian and Ukrainian

Abstract: The use of patient-reported outcome questionnaires is recommended in studies of the orthopaedic field. Reliable, validated tools are necessary to ensure the comparability of results across different studies, centers, and countries. The patient-rated wrist evaluation (PRWE) is a widely accepted and commonly used outcome measure in the self-evaluation after distal radius fractures. The cross-cultural adaptation of PRWE was performed according to international guidelines, following prescribed six stages: translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Similar modifications were reported in other non-English versions, suggesting that some predictable cultural changes can be expected when converting patient questionnaires. 17 We predicted a direct correlation between PRWE-S and the Quick DASH and expected a Spearman coefficient of at least 0.7. The PRWE-S achieved a coefficient of 0.75, which demonstrates good criterion validity.…”
Section: Discussionmentioning
confidence: 80%
“…Similar modifications were reported in other non-English versions, suggesting that some predictable cultural changes can be expected when converting patient questionnaires. 17 We predicted a direct correlation between PRWE-S and the Quick DASH and expected a Spearman coefficient of at least 0.7. The PRWE-S achieved a coefficient of 0.75, which demonstrates good criterion validity.…”
Section: Discussionmentioning
confidence: 80%
“…For instance, many PROMs are translated into multiple languages. The PRWE has been correctly translated into 14 languages, following the translation process described by Beaton et al 50 Nevertheless, we only found cross-cultural validity studies for the Swedish, Hindi, Korean and Danish versions, because the other translated versions were not adequately evaluated. However, our search was limited to English, German and Dutch, so it can be assumed that the cross-cultural validity was evaluated but the results were not published in any of these languages.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the present study are not aware of a systematic comparison of the published translations of the CORE-OM so far. Goldhahn, Shisha, Macdermid, and Goldhahn (2013)…”
Section: Objectivesmentioning
confidence: 99%
“…The authors of the present study are not aware of a systematic comparison of the published translations of the CORE‐OM so far. Goldhahn, Shisha, Macdermid, and Goldhahn () emphasized the importance of “appropriately translated instruments” for “international multicentre studies; or inclusion of people with different cultural backgrounds in national trials” (p. 591). Because the CORE‐OM will be used for international comparisons, we require empirical evidence that the translations can be considered equivalent from a psychometric point of view.…”
Section: Introductionmentioning
confidence: 99%